Correction to "Quaternionic Davis–Wielandt shell in a right quaternionic Hilbert space’’, Ukrainian Mathematical Journal, vol. 75, No. 6, November, 2023 (Ukrainian original vol. 75, No. 6, June, 2023) - Jeribi, Aref; Mahfoudhi, Kamel (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5 We correct a mistake made in the proof of Example 2.1. In fact Tφ,φ_H =0 is not true in the case where T=pmatrix q & 0 0 & -q pmatrix.